The New Heroes : Applause and Sensibilities in the Era of the COVID-19 - Scribano, Adrián Oscar (2020)
Since the implementation of preventive and compulsory social isolation, every night at 9:00 p.m. thousands of Argentines applaud the health system personnel from their patios, balconies and windows in support of their daily tasks.The purpose of this article is to present a critical analysis of the applause that the Argentine population offers as an emotional support for workers in the health sector in times of Covid-19. To achieve this objective, the following argumentative strategy is followed: a) the relationship between heroes and spectators in a spectacularized society is described; b) second, a series of videos of different cities with structural diversity (social class, scale) from the virtual ethnography will be analysed; c) third, applause as an emotion is analysed according to the contexts of its production from the perspective of the sociology of bodies/emotions. Finally, the paper concludes with some questions about the relationship between public health and sensibilities in the post-Covid-19 era.